The effect of Ramadan fasting on serum osmolality in diabetic patients - Vural Keskinler, Mirac; Dincer, Berna; Telci Caklili, Ozge; Oguz, Aytekin (Journal of the Pakistan Medical Association, 2023)
Objective: To observe the changes of osmolarity levels due to fasting in Ramadan among type 2 diabetic patients. Method: The observational study was conducted from May 16 to June 3, 2019, at the Istanbul Medeniyet University, Istanbul, Turkey, and comprised adult type 2 diabetic patients of either gender visiting the diabetes outpatient clinics during the holy month of Ramadan. Those fasting were placed in Group A, while those not fasting formed Group B. Anthropometric measurements and medications in use were recorded. Blood samples were taken in the morning and before the evening meal. Serum osmolality was calculated using serum levels of sodium, glucose and blood urea nitrogen. Data was analysed using SPSS 16. Results: Of the 52 patients, 27(52%) were in Group A and 25(48%) were in Group B. Overall, there were 22(42%) females and 30(58%) males. The mean morning serum osmolalities of the two groups were not different (p>0.05). The mean evening serum osmolality was not significantly different than the mean morning osmolality in Group A (p=0.22). In Group B, the mean evening serum osmolality was significantly lower than the mean morning osmolality (p=0.004). No significant difference was found between mean morning and evening serum osmolalities of those taking sodium-glucose cotransporter 2 (p>0.05). Conclusion: There was no biochemical sign of dehydration with Ramadan fasting in type 2 diabetes mellitus patients. Clinical Trial Number: [NCT04392570] Link: https://clinicaltrials.gov/ Key Words: Fasting, Serum osmolality, Ramadan, Type 2 diabetes mellitus, SGLT-2 inhibitors.